2013
DOI: 10.1128/jb.02300-12
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for the cccA Gene Product, Cytochrome c 2 , in Diverting Electrons from Aerobic Respiration to Denitrification in Neisseria gonorrhoeae

Abstract: Neisseria gonorrhoeae is a microaerophile that, when oxygen availability is limited, supplements aerobic respiration with a truncated denitrification pathway, nitrite reduction to nitrous oxide. We demonstrate that the cccA gene of Neisseria gonorrhoeae strain F62 (accession number NG0292) is expressed, but the product, cytochrome c 2 , accumulates to only low levels. Nevertheless, a cccA mutant reduced nitrite at about half the rate of the parent strain. We previously reported that cytochromes c 4 and c 5 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…Our findings here differ from those of Hopper and colleagues () who reported that mutants expressing c 5 lacking its C‐terminal heme domain and CcoP with a missense mutation disrupting the functionality of its third heme domain retained the ability to reduce nitrite albeit at reduced levels. It remains to be determined whether this disparity relates to differences in methodologies or the strain backgrounds employed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings here differ from those of Hopper and colleagues () who reported that mutants expressing c 5 lacking its C‐terminal heme domain and CcoP with a missense mutation disrupting the functionality of its third heme domain retained the ability to reduce nitrite albeit at reduced levels. It remains to be determined whether this disparity relates to differences in methodologies or the strain backgrounds employed.…”
Section: Discussioncontrasting
confidence: 99%
“…It remains to be determined whether this disparity relates to differences in methodologies or the strain backgrounds employed. Hopper and colleagues () argue for a role for cytochrome c 2 in electron donation to NirK. Interestingly, sequences of c 2 show very high identities for the first 132 amino acids between N. gonorrhoeae and N. meningitidis strains, but there are diverse sequences C‐terminal to this (Finn Erik Aas, Marina Aspholm, unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential target for interaction could be the CydDC complex, a transmembrane complex that functions as a glutathione transporter and that is known to be required for cytochrome bd oxidase activity (53). This would be potentially analogous to the proposed activity of the 56-amino-acid CcoQ subunit of cytochrome oxidase of Neisseria gonorrhoeae, which may bind multiple oxidase-related proteins (54). A third, potentially more intriguing, possibility is that CydX acts as a regulatory subunit of the CydAB complex that has evolved to modify cytochrome bd oxidase activity in certain species of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Class I cytochrome c molecules are small soluble cytochromes that are needed for electron transfer reactions during denitrification in other bacteria (7). In Neisseria gonorrhoeae, the cccA gene product cytochrome c 2 is essential for the shuttling of electrons toward the denitrification machinery (29). Several other unclassified class I cytochromes of D. shibae (Dshi_0508, Dshi_2868) did not influence anaerobic growth (see Table S1).…”
Section: Resultsmentioning
confidence: 99%